How can nudging solve some of the internet data privacy issues - de Almendra Freitas, Cinthia Obladen; Almada, Giovanna Michelato (Direito e Desenvolvimento, 2019)
The development of new technologies often arouses discussions concerning privacy rights. Consequently, when the Internet became popular and worldwide spread, user privacy concerns also began to arise. Therefore, with the emergence of the information society, the notion of user privacy became variable and has changed over time and according to the region. Consequently, its concept has been modified over the decades too. In 1890, privacy was defined as the right to be left alone. As time passed, the idea of privacy has changed and has become more and more multifaceted, as a reflection of intrinsic aspects of the society. Even with the volatility of this concept, privacy is a fundamental right, as well as essential for a citizen to use the Internet properly. Although it is a fundamental right, people tend to give up on their privacy because of functionalities on the Internet or exchange it for small rewards. However, users often do not have the knowledge about the exchanges or violations. In order to solve some of the Internet data privacy issues, Libertarian Paternalism may be used. Different researches were conducted by applying this theory in the data privacy sphere. By using nudges, it is possible to help people choose wisely how to protect privacy, or at least to give them the right amount of information and guide users to the best option.